Racial/Ethnic‐Specific Differences in the Effects of Inhaled Corticosteroid Use on Bronchodilator Response in Patients With Asthma. Issue 5 (23rd July 2019) - Samedy‐Bates, Lesly‐Anne; Oh, Sam S.; Nuckton, Thomas J.; Elhawary, Jennifer R.; White, Marquitta; Elliot, Tyronda; Zeiger, Andy M.; Eng, Celeste; Salazar, Sandra; LeNoir, Michael A.; Meade, Kelley; Farber, Harold J.; et al.
Abstract : American Thoracic Society guidelines recommend inhaled corticosteroid (ICS) therapy, plus a short‐acting bronchodilator, in patients with persistent asthma. However, few prior studies have examined the efficacy of this combination in children of all racial/ethnic groups. We evaluated the association between ICS use and bronchodilator response (BDR) in three pediatric populations with persistent asthma (656 African American, 916 Puerto Rican, and 398 Mexican American children). The association was assessed using multivariable quantile regression. After adjusting for baseline forced expiratory volume in one second and use of controller medications, ICS use was significantly associated with increased BDR only among Mexican Americans (1.56%, P  = 0.028) but not African Americans (0.49%, P  = 0.426) or Puerto Ricans (0.16%, P  = 0.813). Our results demonstrate that ICS augmentation is disproportionate across racial/ethnic groups, where improved BDR is observed in Mexican Americans only. This study highlights the complexities of treating asthma in children, and reinforces the importance of investigating the influence of race/ethnicity on pharmacological response.